2018
DOI: 10.1038/s41598-018-19899-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Transitions and Diffusion Mechanism in DODAB Bilayer

Abstract: Dioctadecyldimethylammonium bromide (DODAB), a potential candidate for applications in drug transport or DNA transfection, forms bilayer in aqueous media exhibiting a rich phase behavior. Here, we report the detailed dynamical features of DODAB bilayer in their different phases (coagel, gel and fluid) as studied by neutron scattering techniques. Elastic intensity scans show dynamical transitions at 327 K in the heating and at 311 K and 299 K during cooling cycle. These results are consistent with calorimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(111 citation statements)
references
References 62 publications
(88 reference statements)
7
103
1
Order By: Relevance
“…The reverse of this transition occurs at TpTm40°normalC (thermal hysteresis Δ T m ≈ 13 °C), as also reported in (Feitosa et al, ). This is in accord with Dubey et al (Dubey et al, ), who reported a melting temperature of 54 °C (and 38 °C as reverse temperature) for DODAB at 70 mM. At this concentration, there are no vesicles but extended bilayers (Feitosa et al, ).…”
Section: Resultssupporting
confidence: 88%
“…The reverse of this transition occurs at TpTm40°normalC (thermal hysteresis Δ T m ≈ 13 °C), as also reported in (Feitosa et al, ). This is in accord with Dubey et al (Dubey et al, ), who reported a melting temperature of 54 °C (and 38 °C as reverse temperature) for DODAB at 70 mM. At this concentration, there are no vesicles but extended bilayers (Feitosa et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Although the structural aspects of almost all the phases of DODAB are explored in detail, [24,25] the hydration properties of the associated water molecules in the close vicinity of the lipid headgroups is relatively less attended in the literature and is one of the motives of the present study. [7] The study reveals slower rotational diffusion of alkyl chain (5.3 10 10 s À1 ) and higher residence time of hydrogen (6.7 ps) in coagel phase compared to those in gel phase (6.8 10 10 s À1 and 5.2 ps). [16] A recent report employing quasi elastic neutron scattering (QENS) and molecular dynamics (MD) simulation studies explored dynamical transition and diffusion mechanism in DODAB bilayer.…”
Section: Introductionmentioning
confidence: 83%
“…[1][2][3] Although the bilayer lamellar states are relevant to biomembranes, non-bilayer lipid phases, such as hexagonal and cubic phases may relate to transient event in the biomembranes including fusion, fission and pore-formation. [7][8][9] DODAB is a bilayer forming lipid, which reveals lamellar structure analogous to biological membrane. [7][8][9] DODAB is a bilayer forming lipid, which reveals lamellar structure analogous to biological membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quasielastic neutron scattering (QENS) has been employed to study DODAB bilayer in coagel, gel and fluid phases [6] with an aim to probe the dynamical transitions and diffusion mechanisms. It has been found that lateral motion of lipids is frozen in the coagel phase, while it's activated in the gel and fluid phases [6]. QENS spectra in the coagel phase are well described considering only the localised motion of the alkyl chains.…”
Section: Introductionmentioning
confidence: 99%